QUANTIFICATION OF METHANE OXIDATION IN THE RICE RHIZOSPHERE USING 13C-LABELLED METHANE - Groot T.T.; van Bodegom P.M.; Harren F.J.M.; Meijer H.A.J. (My University, 2003)
In this paper isotope ratio mass spectrometry is used to determine the methane (CH4) oxidation fraction in the rhizosphere of intact rice plant-soil systems. Earlier studies on quantification of the methane oxidation were based on inhibition or incubation procedures which strongly interfered with the plant-soil system and resulted in a large variability of the reported fractions, while other studies considered stable isotopes at natural abundance levels to investigate methanotrophy in the rhizosphere of rice. The current work is the first that used 13C-labelled CH4 as additive and calculated the oxidation fraction from the ratio between the added 13C-labelled CH4 and its oxidation product 13CO2. Both labelled gases could be distinguished from the natural abundance percentages. The oxidation fraction for methane was found to be smaller than 7%, suggesting that former approaches overestimate the methane oxidation fraction.
Keywords: 13C-LABELLED METHANE; ISOTOPE RATIO; OXIDATION FRACTION; RHIZOSPHERE; RICE; SOIL